2017
DOI: 10.1177/0145445517735492
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Emotion Regulation and Socialization in Behavioral Parent Training: A Proof-of-Concept Study

Abstract: Low-income families are less likely to effectively engage in Behavioral Parent Training (BPT), the standard of care for early-onset (3-8 years old) disruptive behavior disorders (DBDs); however, relatively little is known about predictors of treatment process and outcome within this vulnerable group. Given literature to suggest compromises associated with both low-income status and DBDs, this study examined the role of caregiver emotion regulation and socialization practices in 15 low-income families who parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 55 publications
(76 reference statements)
0
10
0
Order By: Relevance
“…Parents with limited capacity to manage their own emotions may be reluctant to enroll in treatment in the first place, may have more difficulty deploying newly learned coregulation skills when their children are highly distressed, may be less likely to practice skills outside the clinical setting, and/or may be at greater risk for withdrawing from the intervention (Havighurst & Kehoe, 2017; Maliken & Katz, 2013). Indeed, a recent study found that better parental emotion regulation at baseline predicted treatment response to a behavioral parent training intervention for young children with disruptive behavior disorders (Zachary, Jones, McKee, Baucom, & Forehand, 2019). Thus, increased attention is warranted to interventions that include a focus not only on enhancing parents’ abilities to support their children’s navigation of emotional experiences, but on helping them navigate their own as well.…”
Section: Interventions Targeting Parent Emotion Regulationmentioning
confidence: 99%
“…Parents with limited capacity to manage their own emotions may be reluctant to enroll in treatment in the first place, may have more difficulty deploying newly learned coregulation skills when their children are highly distressed, may be less likely to practice skills outside the clinical setting, and/or may be at greater risk for withdrawing from the intervention (Havighurst & Kehoe, 2017; Maliken & Katz, 2013). Indeed, a recent study found that better parental emotion regulation at baseline predicted treatment response to a behavioral parent training intervention for young children with disruptive behavior disorders (Zachary, Jones, McKee, Baucom, & Forehand, 2019). Thus, increased attention is warranted to interventions that include a focus not only on enhancing parents’ abilities to support their children’s navigation of emotional experiences, but on helping them navigate their own as well.…”
Section: Interventions Targeting Parent Emotion Regulationmentioning
confidence: 99%
“…Total scale scores were used in these analyses (α = .93). (Denham & Kochanoff, 2002;Zachary et al, 2019), the current study grouped these subscales into two broader domains including non-supportive responses (CCNES Nonsupportive, including Distress, Minimization, and Punitive Reactions), and supportive responses (CCNES Supportive including Expressive Encouragement, Emotion-focused, and Problem-focused Responses). Higher levels of non-supportive responses to children's emotions represent more maladaptive aspects of emotion socialization processes while higher levels of supportive responses represent more adaptive parental ES.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, standard BPT may indirectly function to improve parent emotion regulation and socialization via a better understanding of “fit” between their own and their child’s behavior and, in turn, to feel more efficacious responding to child behaviors in a more regulated and informed way. To this end, prior work on both PCIT and Helping the Noncompliant Child (HNC; McMahon & Forehand, 2003 ) suggest the potential for improvements in parent emotion regulation and socialization in standard BPT, including improvements comparable to programs targeting those variables in particular (e.g., Lieneman et al, 2019 ; Rothenberg et al, 2019 ; Zachary et al, 2019 ). Yet, we still know little about how certain contextual factors may impact the ways in which BPT treatment effects parent emotion regulation and socialization.…”
mentioning
confidence: 99%
“…Low income generally causes the need to work for every family member. Zachary C determined that in low-income families in Indonesia, the possibility of becoming a low-income family is greater for families with members who do not work [47]. In the female workers from low-income communities, the number of hours they work positively affects their income [48].…”
Section: The Discrepancy Evaluation Model In the Implementation Of On...mentioning
confidence: 99%